Giotto – inventore di iconografie: ancora sul ciclo degli Scrovegni - Valenzano, Giovanna (ASPICE HUNC OPUS MIRUM: zbornik povodom sedamdesetog rođendana Nikole Jakšića, 2020)
The article focuses on some iconographic inventions created by Giotto in the Scrovegni Chapel in Padua. In particular, the author proposes two hypotheses which differ from what has been hitherto suggested. The first concerns the model of the church offered by the client Enrico Scrovegni. Through a series of visual examples, the article demonstrates that Giotto reproposes the iconographic convention already invented by the Roman mosaicists during the early Middle Ages, in which the model shows apse, side elevation and facade in a single image, but this image is renewed, according to a rendition of the vision of the elevations which posits it as a sort of ante litteram axonometry. The second proposal is centred on the figure of the animula holding the Cross in the scene of the Last Judgment. The author suggests a different interpretation of this image, seen as the risen soul of the Wandering Jew, according to the hypothesis formulated by Chiara Frugoni. In fact, it is the soul of Adam who supports the Cross, in the light of some patristic passages that see Christ as the new Adam and a different iconographic tradition, which in any case indissolubly links the Cross to Adam.